Pengaruh Pijat Bayi Dengan Terapi Bunga Lavender Terhadap Pemenuhan Kebutuhan Tidur Neonatus Di Posyandu Melati Mojoroto Kediri - Sri Kasmiatun (Akademi Keperawatan Dharma Husada Kediri, 2014)
Sleeping are unconscious which still work order of succesion siclic and can be brain and body work difference. Sleeping disturb is happened young people but it child and baby disturb happenend. Neonatus until three month to need sleeping time more 20 hour. The purpose of this observation was to know whether there any effect of lavender aroma teraphy baby massage toward neonatus sleeping necesity at the work region of posyandu Melati Mojoroto Kediri. The observation was the pre experiment by using one group pre post test one disign approach. Independen variable is lavender aroma teraphy body massage observation. The population in the observation as many as 13 neonatus and the number of samples as many as 13 neonatus with the sample taking technique was using total sampling. The result was gotten the observation was almost a half 9 neonatus (69,23%) experienced can’t sleeping necesity before lavender aroma teraphy body massage and and most 12 neonatus (92%) can be sleeping necesity after lavender aroma teraphy baby massage. By using t-test was gotten the result, ρ value = 0,001 < α = 0,05, so Ho was rejected. It meant that there was lavender aroma theraphy baby massage toward sleeping necesity at the work region of Posyandu melati Mojoroto Kediri in 2011. It was suggested to mothers to do baby massage at regular time with lavender aroma teraphy so can sleeping neonatus necesity so baby growt age harmony.